THE KARABAKH CONFLICT AS AN IMPORTANT SECURITY ISSUE IN THE SOUTH CAUCASUS - ÖMƏROVA , İlhamə (SSD Journal, 2021)
It was very difficult for the newly independent Republic of Azerbaijan to formulate its national security policy, as well as to define specific security criteria and other criteria within the general security issues of the region in the 1990s. Because, on the eve of the last years of the Soviet Union, incitement of ethnic separatism in its territory and the occupation of its lands by Armenia and so on. Issues such as foreign military intervention and national security were added to the list of problems of nation-building that Azerbaijan has just begun. Over the past thirty years, the Republic of Azerbaijan has demonstrated a principled position to ensure its territorial integrity and national security, as well as increased the economic and military power of our country and its international political prestige. In modern times, with the help of President Ilham Aliyev, Azerbaijan, as a key player in the South Caucasus region, is pursuing an independent foreign policy in difficult and complicated geopolitical conditions, improving its economic system and taking consistent and systematic steps to ensure regional security. As a result of Armenia’s policy of aggression, as well as its foreign policy, it has been left out of all regional projects. Recently, Yerevan’s foreign policy has been failing on a regional scale. Because, Armenia has not been formed as a fool state and is completely dependent on external forces. In this regard, the geopolitical specificity of the situation in the South Caucasus stems from the fact that Armenia poses a threat to the well being, security and sovereignty of neighboring countries in this region. The geopolitical dynamics in the South Caucasus are extremely negatively affected by the Armenian-Azerbaijani conflict over Nagorno-Karabakh. However, by ending the Second Karabakh War with Victory, the Azerbaijani state restored its territorial integrity.